Paraíba agroecológica: elementos de autonomia e reprodução camponesa - Oliveira, Mariana Borba de (2021)
We understand Agroecology as a socio-territorial movement built on a decolonial epistemology and promoted by various sectors of society that seek an alternative against the advance of agribusiness over natural resources and the social rights inherent in the reproduction of life. In this work, we analyze agroecological praxis in Paraíba, based on public policies and local experiences that are articulated in networks and guarantee processes that strengthen agroecological production and expand peasant autonomy. Therefore, we defend the thesis that, in contemporary times, agroecological praxis builds territorial arrangements favorable to the reproduction of the peasant class, and this, as it produces quality food, strengthens the project of food sovereignty, broadly, benefiting the entire population, as defended by rural social movements and Agrarian Reform. We use quantitative and qualitative data to analyze the construction of the Agroecological Movement in Paraíba; some public policies to support Agroecology; the agroecological production and commercialization experiences that favor direct sales to the consumer; and the strategy of Creole seed banks that preserve the genetic and cultural heritage of the peasantry. We conclude that Agroecology strengthens the historical agendas of the peasant class and expands the debate on the Brazilian Agrarian Question, contributing to the transformation of land into peasant territory. The studied experiences are based on cooperation between subjects who resist the monopolization of the territory by capital and have been strengthened in recent decades by public policies. These policies were built based on the participation of social movements and organizations in the decision-making spaces of the federal government. In this way, peasant reproduction (as a condition of autonomy and with food sovereignty) is conditioned to the organization of the peasant class around Agroecology, and is capable of materializing the eco-socialist agendas and values in search of good living.